Analysis of the Effect of Age on Women's Reproductive Health Using the Mixed Method - Nila Hayati; Kamalia Ainun; Niasty Lazmy Zaen; Rizaldy Khair (Science Midwifery, 2022)
The increase in age has a major effect on life expectancy, especially for women, encouraging the wisdom of the elderly population, the increase in the number of the old population is not only interpreted as an increase in the level of welfare and the increase in health conditions but can also be interpreted as a burden because this old age group is no longer productive. Reproductive health problems need to be widely socialized so that women / future mothers know the reproductive problems they will experience and get a way out of these problems. In addition to the influence of age, another thing that affects reproductive health in women is the reproductive health organs themselves. Without knowing the reproductive health organs well, it is feared that the future mothers will be completely blind and may eventually result in the harmony of the husband and wife relationship. reproductive health is a good state of physical, mental and social well-being, not only free from disease or disability, but also healthy from aspects related to the reproductive system, its functions and processes. Based on the results of previous studies, the total population in Tumpatan Nibung Village, Batang Kuis district, is 6,898 people and 1,100 households this number is part of the total population in batang kuis district, Deli Serdang regency. The purpose of this study was to analyze the effect of age on women's reproductive health in Tumpatan Nibung Village, Batang Kuis District, Deli Serdang Regency. The method used in this study is Mixed Method Research (MMR) which is a research method that is applied and tested in terms of outcomes and processes with quantitative and qualitative approaches. The quantitative study population was 250 people, with a sample plan of 158 people. Quantitative analysis in a univariate, bivariate manner using chi-square with multivariate using multiple logistic regression at a confidence level of 95% (α=0.05). The data obtained from the measurement results can be used as an analysis of the next program situation by using test analysis using SPSS on the running system and turning it into an Analysis system as outcomes